2023
DOI: 10.1002/jrsm.1636
|View full text |Cite
|
Sign up to set email alerts
|

A real‐world evaluation of the implementation of NLP technology in abstract screening of a systematic review

Abstract: The laborious and time‐consuming nature of systematic review production hinders the dissemination of up‐to‐date evidence synthesis. Well‐performing natural language processing (NLP) tools for systematic reviews have been developed, showing promise to improve efficiency. However, the feasibility and value of these technologies have not been comprehensively demonstrated in a real‐world review. We developed an NLP‐assisted abstract screening tool that provides text inclusion recommendations, keyword highlights, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Our study further found that LLM-assisted citation screening helped save time in the systematic review process, with a more than 10-fold reduction in the time required to complete the process. Although this finding is consistent with other reports showing the advantage of citation screening using semiautomated screening software, 9 , 10 , 26 eliminating the necessity of inputting key studies would save additional time using LLM-assisted citation screening.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study further found that LLM-assisted citation screening helped save time in the systematic review process, with a more than 10-fold reduction in the time required to complete the process. Although this finding is consistent with other reports showing the advantage of citation screening using semiautomated screening software, 9 , 10 , 26 eliminating the necessity of inputting key studies would save additional time using LLM-assisted citation screening.…”
Section: Discussionsupporting
confidence: 92%
“…Second, LLM-assisted citation may have a higher accuracy than the semiautomated tool. Previous studies on semiautomated citation screening tools reported sensitivity ranging from 0.75 to 0.90, which is comparable with the accuracy of our study; however, our previous research on this tool showed a variable sensitivity of 0.24 to 0.80 for the same dataset used in the present study. Moreover, we found a higher sensitivity of 0.53 to 0.95 with lower variability in the secondary analysis, suggesting the potential advantage of LLM-assisted citation screening for discriminating the relevant literature.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Though the AI-assisted methods developed show promise in studies among previously existing SR and meta-analysis, few have assessed their performance in real-world settings. In a study by Perlmann-Arrow et al, 2022, they developed an NLP-assisted abstract screening tool and evaluated it against a living SR on SARS-CoV2 seroprevalence being updated by investigators [7]. Results showed that the time to complete screening was reduced by 45.9% with a recall of 90%, and a mean user satisfaction rating of 4.2/5.0 when the tool was compared to the two-reviewer approach.…”
Section: Introductionmentioning
confidence: 99%